Preparing the Public Health Workforce : Educational Pathways for the Field and the Classroom - Caron, Rosemary M. (Springer International Publishing : Imprint: Springer, 2015)
In concept and practice, public health casts a wide net, spanning assessment, intervention, and policy; education, prevention, and protection; public, private, and government entities. But key elements are often missing from the picture, including a clear understanding of public health and its goals by the general public, and specific public health education throughout the workforce.                              Public Health Practice responds to these and related challenges by elegantly summarizing the state of the field in an era of dwindling budgets, competing and overlapping services, and a shaky professional infrastructure. In keeping with public health goals set out by the CDC and other leading agencies, the author makes a real-world case for standardizing training, establishing best practices in the field, and coordinating public health systems with their healthcare counterparts. Theory, case examples, tools, and callout boxes highlight knowledge, preparation, and skills professionals need in addressing chronic issues and complex emergencies. Throughout, the emphasis is on greater competency and visibility for the profession, resulting in a more informed, healthier public. Featured in the coverage:                                                                                    Issues in defining the public health workforce.     The state of public health education. Practicing and teaching public health: local, national, and international cases. Standardizing public health practice: benefits and challenges. Integrating public health and healthcare. The future of public health as seen from academia and the frontlines.  Identifying urgent issues and providing cogent answers, Public Health Practice is a call to action for those involved in creating the next level of public health, including professors, practitioners, students, and administrators.